Arthrospira promotes plant growth and soil properties under high salinity environments - Xu, Qiyu; Zhu, Tao; Zhao, Ruifeng; Zhao, Yang; Duan, Yangkai; Liu, Xiang; Luan, Guodong; Hu, Ruibo; Tang, Sanyuan; Ma, Xinrong; Liu, Yan; Li, Shengjun; et al. (Frontiers in Plant Science, 2023)
Salt stress detrimentally impacts plant growth, imperiling crop yield and food quality. Ameliorating plant resilience and productivity in saline environments is critical for global food security. Here, we report the positive effect of Arthrospira (Spirulina) on plant growth and salt tolerance in Arabidopsis and sweet sorghum. Arthrospira application greatly promotes seed germination and seedling growth in both species under salt stress conditions in a dosage-dependent manner. Application of 6 mg This is a provisional file, not the final typeset article Arthrospira per plate significantly enhances K + /Na + equilibrium and reactive oxygen species (ROS) scavenging in Arabidopsis, reducing salt-induced toxicity. The primary root length, survival rate, chlorophyll content, photosynthesis, plant height, biomass and yield were all improved in both species. Concurrently, Arthrospira demonstrated the synthesis of compatible solutes, such as trehalose (Tre) and glucosylglycerol (GG), contributing to heightened stress tolerance when cocultivated with Arabidopsis on plates. Transcriptome analysis revealed dramatic up-/downregulation of genes involved in phytohormone signal transduction, chlorophyll and photosynthesis metabolism, and phenylpropanoid metabolism in Arabidopsis. Furthermore, the application of Arthrospira exerted a positive influence on the rhizosphere bacteriome structure in sweet sorghum, crucial for nutrient cycling and soil health enhancement. Our findings uncovered the underlying mechanisms of algae-plants interaction in saline soil, proposing strategies to enhance crop productivity and soil quality, thereby addressing the urgent need for sustainable agriculture practices to mitigate salinity's repercussions amidst climate change challenges.